If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/4(12x-8)=-6
We simplify the equation to the form, which is simple to understand
3/4(12x-8)=-6
Reorder the terms in parentheses
+(+9x-6)=-6
Remove unnecessary parentheses
+9x-6=-6
We move all terms containing x to the left and all other terms to the right.
+9x=-6+6
We simplify left and right side of the equation.
+9x=0
We divide both sides of the equation by 9 to get x.
x=0
| 4x+17.5=49.5 | | 4/7(2-x)=8 | | 5x^2-3x-4-7x+8-4x^2= | | 5(3+10u)= | | X*54=100 | | -10(b-5)=-70 | | 1/2x-4=-1/2x+4 | | Y=2(2y-12)+1 | | 7x-3.5=28 | | x+0.00398x=1 | | -10(b-5)=-60 | | -10(b-5)=-50 | | Y=2(2y-12) | | X-3y=41 | | 5z+15=25 | | -10(b-5)=-100 | | 3(n+44)=18 | | -10(b-5)=-1000 | | 8(3x+2)=50 | | 3a+6=6a-5 | | 4(2a+6)=80 | | 9x-3x-4x= | | 43=x+.08625x+.2x | | -10(b+5)=-1000 | | 9x-3x-4x=0 | | 9/877x=49.67 | | -50(b+5)=-1000 | | 10y-7=73 | | -2/3(4x-7)=14 | | 4x+20=44 | | 3x^2-2x-6-8x+7-2x^2= | | 7(t+4)-3(t+5)=13 |